Collaborating with People Like Me: Ethnic Coauthorship within the United States - Freeman, Richard B.; Huang, Wei (Journal of Labor Economics, 2015)
By examining the ethnic identity of authors in over 2.5 million scientific papers written by US-based authors from 1985 to 2008, we find that persons of similar ethnicity coauthor together more frequently than predicted by their proportion among authors. The greater homophily is associated with publication in lower-impact journals and with fewer citations. Meanwhile, papers with authors in more locations and with longer reference lists get published in higher-impact journals and receive more citations. These findings suggest that diversity in inputs by author ethnicity, location, and references leads to greater contributions to science as measured by impact factors and citations.